Tagalog qanggiq ‘a pet name’ - Lopez, Cecilio (The Archive; Vol 1 (1977): Publication One: Selected Writings of Cecilio Lopez in Philippine Linguistics, 2025)
There is a rich bibliography on the splitting of proto-phonemes in AN languages. Brandes called attention to the necessity of explaining not only deviations of irregular forms but also of doublets (dubbelvormen) which are the result of the splitting in several phonemes of the original pronunciation of a word in the course of time, and which became fixed and gave rise to certain alteration in meaning. Conant found a large number of r/g variants in Ilk vocabulary. Dyen gave instances of assumed d/l doublets in Tag resulting from the splitting of a proto-phoneme. According to Dahl *ɣ  split in j and zero with the latter occurring more frequently than the former in Mnj than in Mlg. Cases of splitting, doublets, alternation and interchange of phonemes are found in the articles by Biggs, Cowan, Elbert, Izui, Holmer and Milner in Indo-Pacific linguistic studies, Part I (1965). In this paper I will discuss qangqíq, a possible doublet with homorganic nasal combination of qali with an oral consonant, from *'a(ŋ́)g'i'  ’kin, relative (mostly younger)’.